Current evidence and future perspectives in the exploration of sleep-related eating disorder–a systematic literature review - Vasiliu, Octavian (Frontiers in Psychiatry, 2024)
Sleep-related eating disorder (SRED) is a non-REM parasomnia with potentially significant negative effects on general health (dangerous activities during night eating episodes, obesity, or metabolic syndrome, for example). Although the history of SRED encompasses more than six decades, public awareness and even the awareness of the mental health specialists of this disorder is very limited, a phenomenon that hinders the development of research in this field. Therefore, a systematic review based on PRISMA 2020 guidelines explored the available evidence for SRED found in four electronic databases (PubMed, Cochrane Collaboration, Google Scholar, and Clarivate/Web of Science). A number of 94 primary and secondary reports were retrieved, investigating aspects regarding the risk factors, epidemiology, clinical data and differential diagnosis, epidemiology, structured evaluation, and treatment of SRED. Based on the results of these reports, Z-drugs, but also certain benzodiazepines, antidepressants, antipsychotics, and psychostimulants may trigger the onset of SRED. Psychiatric and neurologic disorders have also been associated with SRED, either as risk factors or comorbid conditions. Cerebral glucose metabolism dysfunctions, neurotransmitter dysfunctions, and genetic factors have been invoked as pathogenetic contributors. Structured assessment of SRED is possible, but there is a dearth of instruments dedicated to this purpose. Data on the prevalence and treatment of SRED exist, but good-quality epidemiological studies and clinical trials are still missing. In conclusion, future research is expected to address the shortcomings of SRED exploration by creating the conditions for better quality and larger group clinical research. The need for such investigation is granted by the importance of this pathology and its negative functional consequences.